2020
DOI: 10.1080/25725084.2020.1788200
|View full text |Cite
|
Sign up to set email alerts
|

Maritime piracy operations: Some legal issues

Abstract: The international legal regime pertaining to maritime piracy has developed and grown over the years. These changes were prompted due to lacunas in the legal system, which surfaced when the codified laws were implemented. The problem of maritime piracy flares up every few years, especially with the modernization of boats and weapons. Dealing with maritime piracy involves coordinated and orchestrated efforts at different levels including, domestic, regional and international. Anti-maritime piracy operations have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…Another study applied a Fuzzy AHP and found that international convention and policy, defense strategies when sailing, hardware and software, security plan, response ability, and communication facilities are the main elements that need to be considered to minimize piracy attacks (Tseng et al, 2021 ). Studies also suggested that anti-piracy operations, regulations and policies as well as coordination at domestic, regional, and international level enable the minimization and control of piratical activities (Ahmad, 2020 ). The presence of naval bases is crucial in supporting maritime forces combat piracy (Danzell et al, 2023 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Another study applied a Fuzzy AHP and found that international convention and policy, defense strategies when sailing, hardware and software, security plan, response ability, and communication facilities are the main elements that need to be considered to minimize piracy attacks (Tseng et al, 2021 ). Studies also suggested that anti-piracy operations, regulations and policies as well as coordination at domestic, regional, and international level enable the minimization and control of piratical activities (Ahmad, 2020 ). The presence of naval bases is crucial in supporting maritime forces combat piracy (Danzell et al, 2023 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the legal regulation and measures of piracy, for example, some scholars have studied the reasons why Indonesia does not join the Asian regional cooperation agreement on combating piracy and armed robbery against ships [9]; some scholars hold the belief that countries should revise their domestic definition of piracy [10]; exploring the definition of piracy in the United Nations Convention on the law of the sea [11], sorting out the evolution of the concept of piracy [4], analyzing and describing the judgment of piracy cases of a certain county [12], outlining the different initiatives taken by the international community to combat piracy in Somalia [13]. Some scholars point out that insufficient international laws to solve the problem of territorial piracy, coupled with the lack of effective law enforcement in the special political, social, and economic conditions in some countries, resulting in a surge in piracy in their territorial waters [14]; some scholars have explored the purposes of piracy crime [15,16]; some scholars have also explored the legislative model of piracy [17], etc.…”
Section: Piracy Legal Regulation and Measuresmentioning
confidence: 99%
“…I would like to express my gratitude to the International Maritime Administration for providing pirate data for this article in recent ten years, which led to the conception and writing of this article. 10 Wireless Communications and Mobile Computing…”
Section: Acknowledgmentsmentioning
confidence: 99%
“…The International Law Commission (ILC) clarified that animo furandi is not essential, as piracy may be perpetrated out of anger or vengeance. 32 Private ends are distinguished from political motives. However, in practice, it is difficult to distinguish between private and politically motivated objectives.…”
Section: Private Ends Requirement Private Endsmentioning
confidence: 99%